The electrophysical and optical properties of gadolinium monoantimonide thin films - Jabua, Z.; Kupreishvili, I.; Gigineishvili, A.; Iluridze, G.; Minashvili, T. (Физическая инженерия поверхности, 2012)
Within a wide temperature interval 90 – 700 K the main the dependence of electro-physical parameters
of GdSb films (specific resistance, Hall constant and thermo-electromotive force) on temperature
have been measured. It has been shown that the films are semimetals. The reflection and adsorption
spectra of prepared films have been studied for the first time within the intervals of 0.05 – 5.5 eV. On
the basis of received data the diagram of the dependence of penetration real part and loss functions
on the photon energy have been plotted. It has been shown that the spectra of optical parameters
have quite a complex nature. Разработана технология приготовления тонких кристаллических плёнок GdSb методом вакуумно-термического испарения из двух независимых источников Gd и Sb, в широком интервале
температур 90 – 700 K. Исследованы температурные зависимости удельного электросопротивления, постоянной Холла и термо-ЭДС. Показано, что пленки являются полуметаллами. В
области энергии фотонов 0.05 – 5.5 эВ измерены спектры отражения и поглощения. В результате
полученных данных вычислены энергетические зависимости деиствительной и мнимой части
диэлектрической проницаемости, а также функции потерь. Исследования выявили сложный
характер оптических параметров изготовленных плёнок. Розроблена технологія приготування тонких кристалічних плівок GdSb методом вакуумнотермічного випаровування із двох незалежних джерел Gd і Sb, у широкому інтервалі температур
90 – 700 K. Досліджені температурні залежності питомого електроопору, постійної Хола і термо-ЕРС. Показано, що плівки є напівметалами. В області енергії фотонів 0.05 – 5.5 еВ виміряні
спектри відбиття і поглинання. У результаті отриманих даних обчислені енергетичнізалежності
дійсної та уявної частини діелектричної проникності, а такожфункції втрат. Дослідження виявили
складний характер оптичних параметрів виготовлених плівок.